PENERAPAN MEDIA PEMBELAJARAN KARTU DOMINO UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VII SMP NEGERI - Muthi, Amirah Zahra; Sujarwo, Sujarwo; Hidayaht, Achmad Nur (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
This research aims to improve the learning outcomes of seventh-grade IPS (Social Studies) students at SMPN 236 Jakarta through the implementation of domino card learning media. The educational problem identified was low learning outcomes due to less innovative learning methods. This study employed the Kemmis-McTaggart spiral model of Classroom Action Research (CAR), conducted in three cycles, encompassing planning, action, observation, and reflection. The research subjects were 34 students from class VII-C. Data were collected through observation, tests (cognitive scores), and interviews. The results showed a significant improvement in the cognitive domain, with learning outcomes reaching 67.6% in Cycle I, 79.4% in Cycle II, and 85.2% in Cycle III, surpassing the Minimum Completeness Criteria (KKM) of 75 and classical completeness of 80%. Furthermore, there was an increase in student engagement in the affective domain, particularly in questioning and collaboration skills. Domino cards proved effective in presenting material contextually and fostering collaboration. Thus, the application of GBL (Game-Based Learning) assisted by domino cards successfully improved students' learning outcomes and engagement in Social Studies. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar IPS siswa kelas VII-C SMPN 236 Jakarta melalui penerapan media pembelajaran kartu domino. Permasalahan pendidikan yang ditunjukkan merupakan rendahnya hasil belajar akibat pembelajaran yang kurang inovatif. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) model spiral Kemmis-Mc.Taggart yang dilaksanakan dalam tiga siklus, meliputi perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian adalah 34 siswa kelas VII-C. Data dikumpulkan melalui observasi, tes (nilai kognitif), dan wawancara. Hasil penelitian menunjukkan peningkatan signifikan pada ranah kognitif, dengan hasil belajar mencapai 67,6% pada Siklus I, 79,4% pada Siklus II, dan 85,2% pada Siklus III, melampaui KKM 75 dan ketuntasan klasikal 80%. Selain itu, terdapat peningkatan keaktifan siswa pada ranah afektif, khususnya dalam kemampuan bertanya dan bekerja sama. Kartu domino terbukti efektif dalam menyajikan materi secara kontekstual dan mendorong kolaborasi. Dengan demikian, penerapan GBL berbantuan kartu domino berhasil meningkatkan hasil belajar dan keaktifan siswa IPS.